Physical properties of novel -fe2o3/nio heterostructures through immersion/ solgel spin coating method: Different deposition numbers of nio layer - Suriani Abu Bakar (Tanjong Malim, 2021)
Physical properties of novel -fe2o3/nio heterostructures through immersion/ solgel spin coating method: Different deposition numbers of nio layer by Suriani Abu Bakar